IJCM_276A: Determinants of Delayed Sputum Conversion among Tuberculosis Patients in Malappuram District: A Case Control Study - Rajeev Krishnaraj; Sebastian NM (Wolters Kluwer Medknow Publications, 2024)
Background: Treatment of drug-sensitive TB consists of an intensive phase of 2 months followed by a continuation phase of 4 months. After completion of intensive phase of therapy, sputum AFB smear microscopy is repeated and presence of smear conversion is suggested as a significant early predictor of treatment effectiveness. Delay in sputum conversion will lead to prolongation of the period of time that patients remain contagious. Objectives: To study the determinants of delayed sputum conversion among Tuberculosis patients in Malappuram district Methodology: A Case control study was conducted among tuberculosis patients residing in Malappuram district of Kerala and registered under NTEP in District Tuberculosis Centre (DTC), Manjeri, Malappuram. After satisfying inclusion and exclusion criteria, 90 tuberculosis patients who failed to achieve sputum smear negativity after completion of 2 months of intensive phase multi drug therapy were taken as cases. Another 90 tuberculosis patients those who achieved sputum smear negativity after completion of 2 months of intensive phase therapy were selected as control group. Data was collected by interview method. Results: Patients with lower socio-economic status (OR = 3.59, 95% CI 1.92- 6.73), low BMI or underweight (OR = 1.98, 95% CI 1.1 - 3.6), multiple symptoms (OR= 5.50, 95% CI 1.98 - 15.28), increased duration of symptoms (OR=4.54, 95% 2.24-9.19), co-morbid condition of diabetes mellitus (OR = 2.25, 95% CI 1.24 - 4.09) are at statistically significant risk of delay in sputum smear conversion after intensive phase of anti-tubercular therapy. Conclusion: Patients with lower socio-economic status, low BMI or underweight, multiple symptoms, increased duration of symptoms, co-morbid condition of diabetes mellitus are at statistically significant risk of delay in sputum smear conversion after intensive phase of anti-tubercular therapy. Treating physicians and public health experts should give special attention to TB patients with these risk factors.